Social recruitment in HRM : a theoretical approach and empirical analysis - Gravili, Ginevra; Fait, Monica (The changing context of managing people, 2016)
This book was born from the desire to analyze the role of social recruitment in human resources management. The first chapter analyzes theoretical background of social media communication and focuses on the trend to make use of these instruments in SMEs and public and non-profit sectors. The second chapter explores an analysis of social sphere through three perspectives: a) how it has changed the identity of individuals; b) the relationship between social media and aspects of personality; c) the correlation between social media and cultural dimensions. The third chapter, focuses on the advantages and limitations of social recruitment and examines how employer branding can used strategically in order to attract potential candidates. The relationship between social network and recruitment has been analyzed through empirical research on public and non-profit sector and SMEs (using Cranet data) in the fourth chapter. The last chapter analyzes the competitive advantage which social recruitment can generate.